INTEGRATING CIRCULAR ECONOMY (CE) PRACTICES INTO UNIVERSITY MANAGEMENT IN NIGERIA - Adeoye OluwaToyin Temitope; Hayatu Sa’adatu Jauro; David Esther; Miriam Odinaka Onouha (ANTIS PUBLISHER, 2025)
Objective: The study examined circular economy (CE) Practices that University Management should adopt to enhance sustainable university education in Nigeria. The study used secondary data. The secondary data were collected from both print and online publication. The study concluded that cycling, reuse, eco-design, and sustainable procurement are some of the circular economy (CE) practices that university management can adopt to ensure sustainable university education across Nigeria. Resting on these findings, it is suggested that the paper recommends that the Nigerian universities need to put institutional policies that instil the principles of the circular economy in all facets of the management and operations of the institutions. These models should be the ways of waste minimizing, sustainable resources management, recycling and eco-innovation. The management of the university is also supposed to harmonize these policies with the national sustainability programs and international programs like the United Nations Sustainable Development Goals (SDGs). A specific policy direction would give a sense of direction on how to be implemented, who will be held accountable and performance assessment at departmental levels. Universities ought to establish concepts of CE in academic courses in different fields such as engineering, business, environmental sciences, and social sciences. This collaboration will contribute to the development of the sustainability-based mentality among students and personnel. Also, the institutions are to encourage waste valorization, sustainable product design, renewable energy, and green technologies research and innovation. The practical implementation and interdisciplinary collaboration may be supported additionally by the creation of CE research centers or hubs. Universities ought to introduce effective waste segregation, recycling and composting measures to reduce land fill disposal. An audit of waste should be periodically done to come up with the significant waste streams and come up with measures of recovering the material. Collaborations with recycling companies and local community can strengthen collection, processing and reuse activities. Furthermore, universities can serve as models by demonstrating zero-waste campus initiatives and creating incentives for departments that effectively manage their waste streams.